(Mes-Acr-Me)+ClO4– Catalyzed Visible Light-Supported, One-Pot Green Synthesis of 1,8-Naphthyridine-3-Carbonitriles - Tabassum, Sumaiya; Govindaraju, Santhosh; Kendrekar, Pravin (Topics in catalysis, 2025)
A novel, four-component one-pot green synthesis of biologically active 1,8-naphthyridines by a reaction of diverse aromatic aldehyde, malononitrile, 4-hydroxy substituted 1,6-dimethylpyridin-2(1 H )-one, corresponding aniline in EtOH catalyzed by 9-Mesityl-10-methylacridinium perchlorate [(Mes-Acr-Me) + ClO 4 – ] under visible light generated from a 24 W Blue LED wavelength 450–460 nm at 26 °C is reported. In contrast with the reported procedure, our methodology is diverse, versatile and has several favourable factors such as metal-free, excellent yields, shorter reaction durations, chromatography free and straightforward extraction process. Graphical Abstract